Dendritic Cells From the Cervical Mucosa Capture and Transfer HIV-1 via Siglec-1 - Perez-Zsolt, Daniel; Cantero-Pérez, Jon; Erkizia, Itziar; Benet, Susana; Pino, Maria; Serra-Peinado, Carla; Hernández-Gallego, Alba; Castellví, Josep; Tapia, Gustavo; Arnau-Saz, Vicent; Garrido, Julio; Tarrats, Antoni; et al. (Frontiers in Immunology, 2019)
Antigen presenting cells from the cervical mucosa are thought to amplify incoming HIV-1 and spread infection systemically without being productively infected. Yet, the molecular mechanism at the cervical mucosa underlying this viral transmission pathway remains unknown. Here we identified a subset of HLA-DR+ CD14+ CD11c+ cervical DCs at the lamina propria of the ectocervix and the endocervix that expressed the type-I interferon inducible lectin Siglec-1 (CD169), which promoted viral uptake. In the cervical biopsy of a viremic HIV-1-infected patient, Siglec-1+ cells harbored HIV-1-containing compartments, demonstrating that in vivo, these cells trap viruses. Ex vivo, a type-I interferon antiviral environment enhanced viral capture and trans-infection via Siglec-1. Nonetheless, HIV-1 transfer via cervical DCs was effectively prevented with antibodies against Siglec-1. Our findings contribute to decipher how cervical DCs may boost HIV-1 replication and promote systemic viral spread from the cervical mucosa, and highlight the importance of including inhibitors against Siglec-1 in microbicidal strategies.